2013
DOI: 10.4238/2013.june.13.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Vriesea cacuminis (Bromeliaceae): an endangered and endemic Brazilian species

Abstract: ABSTRACT. Data about the genetic structure can help to understand the evolutionary process of natural populations as well as to drive strategies of conservation. Vriesea cacuminis, an endemic Brazilian Bromeliad, has been found in 2 areas of Minas Gerais State. One is a legal preservation unit (Ibitipoca State Park) and the other an unprotected area (Serra Negra). The 2 areas belong to the Mantiqueira Mountain Range Complex; both are characterized by steep relief with high altitudes and by heterogenic vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…Great intraspecific genetic variability can be seen in P. flammea due to the high percentage of polymorphic bands (PBP). In bromeliads, a similar result was reported by Ribeiro et al (2013), who studied the genetic diversity in Vriesea cacuminis with 16 ISSR primers and observed 87% polymorphism. However for the same gender studied in this work, Domingues et al (2011) identified low polymorphism (35%) with molecular markers of endangered natural populations.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Great intraspecific genetic variability can be seen in P. flammea due to the high percentage of polymorphic bands (PBP). In bromeliads, a similar result was reported by Ribeiro et al (2013), who studied the genetic diversity in Vriesea cacuminis with 16 ISSR primers and observed 87% polymorphism. However for the same gender studied in this work, Domingues et al (2011) identified low polymorphism (35%) with molecular markers of endangered natural populations.…”
Section: Resultssupporting
confidence: 69%
“…This AMOVA partition showed greater genetic variation within the population, with 90.3% of the total variation, and the remaining 9.7% of the genetic variation was observed among populations. According to Ribeiro et al (2013), greater intra-population genetic diversity suggests the division of smaller amounts of main groups, as observed in this study. The amount of genetic differentiation of populations (Φ ST ) was 0.0974, indicating moderate genetic differentiation, obtained by AMOVA, and was significant (P < 0.001) with probabilities calculated per 1000 random permutations.…”
Section: Resultssupporting
confidence: 58%
“…This outcrossing species is morphologically related to V. minarum ( Versieux, 2011 ), and its low population genetic structuring was related to clone longevity and connection among populations by efficient pollinators. The authors of this study interpreted this last factor as the main cause of the low structure and high diversity indices observed ( Ribeiro et al, 2013 ).…”
Section: Conservation -mentioning
confidence: 68%
“…Lack of population structuring using inter-simple sequence repeat (ISSR) markers was reported by Ribeiro et al (2013) in Vriesea cacuminis L.B. Sm., another rare rupicolous species from Minas Gerais.…”
Section: Conservation -mentioning
confidence: 99%
“…However, this information is important for endangered species like D. meziana (Ministério do Meio Ambiente, 2014;Schütz, 2014). It can contribute to our understanding of microevolutionary processes of natural populations, assist in the delimitation of species and subspecies (Palma-Silva et al, 2011), and help to detect hybridization (Zanella et al, 2016) and to design management and conservation strategies (Ribeiro et al, 2013). Here, we present 15 polymorphic microsatellite loci developed for the genus Deuterocohnia using 454 pyrosequencing technology.…”
Section: Ofmentioning
confidence: 99%